Protein Quality Control and the Amyotrophic Lateral Sclerosis/Frontotemporal Dementia Continuum - Shahheydari, Hamideh; Ragagnin, Audrey; Walker, Adam K.; Toth, Reka P.; Vidal, Marta; Jagaraj, Cyril J.; Perri, Emma R.; Konopka, Anna; Sultana, Jessica M.; Atkin, Julie D. (Frontiers in Molecular Neuroscience, 2017)
Protein homeostasis, or proteostasis, has an important regulatory role in cellular function. Protein quality control mechanisms, including protein folding and protein degradation processes, have a crucial function in post-mitotic neurons. Cellular protein quality control relies on multiple strategies, including molecular chaperones, autophagy, the ubiquitin proteasome system, endoplasmic reticulum (ER)-associated degradation (ERAD) and the formation of stress granules (SGs), to regulate proteostasis. Neurodegenerative diseases are characterized by the presence of misfolded protein aggregates, implying that protein quality control mechanisms are dysfunctional in these conditions. Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are neurodegenerative diseases that are now recognized to overlap clinically and pathologically, forming a continuous disease spectrum. In this review article, we detail the evidence for dysregulation of protein quality control mechanisms across the whole ALS-FTD continuum, by discussing the major proteins implicated in ALS and/or FTD. We also discuss possible ways in which protein quality mechanisms could be targeted therapeutically in these disorders and highlight promising protein quality control-based therapeutics for clinical trials.